2017
DOI: 10.5194/acp-17-5311-2017
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fuel ethanol content on primary emissions and secondary aerosol formation potential for a modern flex-fuel gasoline vehicle

Abstract: Abstract. The effect of fuel ethanol content (10, 85 and 100 %) on primary emissions and on subsequent secondary aerosol formation was investigated for a Euro 5 flex-fuel gasoline vehicle. Emissions were characterized during a New European Driving Cycle (NEDC) using a comprehensive set-up of high time-resolution instruments. A detailed chemical composition of the exhaust particulate matter (PM) was studied using a soot particle aerosol mass spectrometer (SP-AMS), and secondary aerosol formation was studied usi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
39
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 80 publications
6
39
1
Order By: Relevance
“…Most of the PM emitted by GDI vehicles is found to be EC (on average 80%; range: 45-95%). The high EC content is consistent since the introduction of GDIs in the markets: from early 2000s [93,95] to 2010s [94,100,[102][103][104][105][106][107][108][109]. The vehicle to vehicle variability masks any influence of test cycle, position of the injectors (side or top), or fuel injection strategy (stratified or stoichiometric) on the relative contribution of EC to PM.…”
Section: Chemical Compositionmentioning
confidence: 91%
See 1 more Smart Citation
“…Most of the PM emitted by GDI vehicles is found to be EC (on average 80%; range: 45-95%). The high EC content is consistent since the introduction of GDIs in the markets: from early 2000s [93,95] to 2010s [94,100,[102][103][104][105][106][107][108][109]. The vehicle to vehicle variability masks any influence of test cycle, position of the injectors (side or top), or fuel injection strategy (stratified or stoichiometric) on the relative contribution of EC to PM.…”
Section: Chemical Compositionmentioning
confidence: 91%
“…The following studies were considered in the figures of the main text. Figure 1 (upper panel): PM PFI: [42,91,[93][94][95][96]100,101,121, Figure 1 (lower panel): PM GDI: [37,42,51,68,74,[93][94][95]100,[102][103][104][105][106]108,109,120,121,132,[157][158][159][160][161][162][163][165][166][167]169,170,173,[175][176][177][178][179]181,…”
Section: Appendix Bmentioning
confidence: 99%
“…Field and laboratory experiments have demonstrated that the presence and properties of nucleation mode particles in vehicle emissions depend on multiple factors, including the vehicle engine and emission after-treatment technologies, driving conditions, used fuels and lubricant oils, and ambient meteorological conditions (e.g. Lee et al 2015, Karjalainen et al 2016b, 2016c, Saliba et al 2017, Timonen et al 2017. A further complication arises from the observations that the nucleation mode particles associated with motor vehicle emissions may contain a non-volatile core (Sgro et al 2008, Lähde et al 2009.…”
Section: Npf Associated With Transportationmentioning
confidence: 99%
“…However, longer times for the stabilization of the SP-AMS concentration would have been advantageous for the reliability of ammonium and, as a consequence, nitrate particle formation. Karjalainen et al (2016) and Timonen et al (2017) estimated the effect of particle losses in a similar PAM chamber to be small. The particle losses measured by Karjalainen et al (2016) depend on particle size and are below 10 % at the particle sizes with most particle mass.…”
Section: Pam Artifacts and Lossesmentioning
confidence: 99%